Design, Operation and Evaluation of Mobile Communications: First International Conference, MOBILE 2020, Held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings - Salvendy, Gavriel; Wei, June (LNCS Sublibrary: SL 3, Information Systems and Applications, incl. Internet/Web, and HCI, 2020)
This LNCS 12216 constitutes the refereed proceedings of the First International Conference on Design, Operation and Evaluation of Mobile Communications, MOBILE 2020, held as part of HCI International 2020 in Copenhagen, Denmark in July 2020.The conference was held virtually due to the corona pandemic. The total of 1439 papers and 238 posters included in the 40 HCII 2020 proceedings volumes was carefully reviewed and selected from 6326 submissions. The regular papers of Design, Operation and Evaluation of Mobile Communications, MOBILE 2020, presented in this volume were organized in topical section around the subject:  Design, Operation and Evaluation of Mobile Communications.